Deformation Dependent Sound Absorption Property of a Novel Magnetorheological Membrane Sound Absorber - Sun, Chuanlin; Cao, Xufeng; Zhou, Xiaoling; Gong, Xinglong; Xuan, Shouhu (Frontiers in Materials, 2020)
A novel membrane sound absorber based on the magnetorheological membrane (MRM) is developed for active sound absorption. Due to its good flexibility and stretch-ability, the MRM consisting of carbonyl iron particles (CIPs) and polydimethylsiloxane (PDMS) elastomer matrix can be easily deformed. The deformation of MRM is investigated by the digital image correlation method. The off-plane displacement is positively related to both of the CIPs mass fractions and magnetic field strength. The sound absorption performance of MRM sound absorber is investigated and it is found that the thickness of the membrane, CIPs mass fractions, and air cavity length behind the membrane significantly influence the sound absorption performance. The magnetic field can adjust the sound absorption frequency without affecting the high acoustical absorption coefficients. The double-layer membrane structure has two sound absorption peaks within the testing frequency range and further improves the frequency adjustability of the sound absorber. Therefore, it is expected to be a particularly promising alternative for active sound absorption. Finally, the numerical solutions calculated by the equivalent circuit method also support the experimental results.